The Influence of Genetic Variations in CYP1A2 Associated with Clozapine Metabolism in Schizophrenia Patients - Fathina Annajla; Annisa Frastica Septi; Nanda Diva Meilani; Aurora Fatimatuz Zahro (Universitas Labuhanbatu, 2024)
Schizophrenia is a severe mental disorder that affects how a person thinks, feels, and behaves. Antipsychotic drugs are the treatment of choice for patients with schizophrenia. Clozapine is an atypical antipsychotic with unique efficacy in treatment-resistant schizophrenia. However, genetic variations in CYP1A2 can influence the differences in the activity of this enzyme, which in turn can affect the metabolism of clozapine and the response to treatment. This review aims to examine the impact of CYP1A2 genetic variations on clozapine metabolism in patients with schizophrenia. This review is prepared using the narrative literature review method, literature search was conducted through PubMed over the past ten years (2014-2024) using relevant keywords. The findings indicate that CYP1A2 genetic variations *1F is an ultrarapid metabolizer whose activity is strengthened by the presence of cigarettes, while *1C and *1D shows a decrease in CYP1A2 enzyme metabolism. This review underscores the importance of considering genetic factors, particularly CYP1A2, in tailoring treatment plans for schizophrenia patients